Model of a Quinary Structure between Krebs TCA Cycle Enzymes: A Model for the Metabolon - Vélot, Christian; Mixon, Mark B; Teige, Markus; Srere, Paul A (Biochemistry (Easton), 1997)
The enzymes which are responsible for catalyzing sequential reactions in several metabolic pathways have been proposed to be highly organized in supramolecular complexes termed metabolons. However, the in situ existence of these weak complexes is difficult to demonstrate because many of them are dissociated during isolation due to dilution effects. Consequently, the metabolon concept is subject to controversy. A model system consisting of genetically prepared bienzymatic fusion proteins has been used to immobilize sequential metabolic enzymes in close proximity and to demonstrate possible kinetic advantages of metabolons. These experiments use the sequential Krebs TCA cycle enzymes from yeast mitochondrial malate dehydrogenase (MDH), citrate synthase (CS), and aconitase (ACO). Using the porcine high-definition structures of these three enzymes, we have performed computer-modeling studies in order to understand how the molecules may interact. Among the thousands of docking orientations we have tried, one was found to respond to the structural and experimental constraints from the results obtained with the yeast fusion proteins. Interestingly, this quinary structure model shows substantial interacting surface areas with spatial and electrostatic complementarities which make the complex thermodynamically stable. This structure also contains an unbroken electrostatically favorable channel connecting the active sites of ACO and CS, as well as the one previously reported between CS and MDH active sites. Charged amino acids which could be involved in interactions stabilizing the complex have been identified. This model will be used as the basis for further experimental work on the structure of the Krebs TCA cycle metabolon.